The Unbearable Opacity of How MCPS Writes to Parents - Dasgupta, Sunil; Ricci, Michael (I Hate Politics Podcast, 2025)
One of the biggest complaints against Montgomery County Public Schools, the largest school district in Maryland and 17th nationwide, is communication style. When Superintendent Thomas Taylor took office in 2024 set a new tone with a funny snow day video, but as the school district seeks a major overhaul of school attendance boundaries, the school district is losing control over its strategy and communications. Sunil Dasgupta talks to Michael Ricci, a MCPS parent and former communications director for Governor Larry Hogan and US House Speakers Paul Ryan and John Boehner, about MCPS’ inscrutable style and how to fix the problem. Music by Anna Rubin.
Keywords: I Hate Politics